INSTITUTIONAL DIMENSION OF BUSINESS CLUSTER - Bembenek, Boguslaw (European Scientific Journal, ESJ, 2015)
To achieve dynamic sustainable development in the contemporary domestic and world economy it is important to develop business clusters which create emerging industries and help to build social capital. In this article the author considers the institutional logic of business cluster and the nature of the transactions process between the members of this structure. The aim of the article was to show that clusters on the one hand are examples of institutions, and on the other hand they co-create institutions that enable the members of the cluster to satisfy their needs, regulate their activity, ensure the continuity of cooperation and integrate members around common goals and values. Dual approach to institutions indicates in this case that their function is to control and trigger the activities in the cluster. The paper presents a business cluster as an example of an institution which plays an essential role in contemporary socio-economic processes. It attempts also analysing the importance of clustering from the perspective of the theory of transaction costs, considering that the business cluster is always seen as a privileged place for the creation of social networks among firms because of the presence of trust and partnership in the economic transactions of colocated actors that is facilitated by their proximity. The author stressed that the business cluster has a beneficial impact on the reduction of opportunistic attitudes of cluster members – and owing to this – on the decrease in transaction costs.